Electrospinning of a Copolymer PVDF-co-HFP Solved in DMF/Acetone: Explicit Relations among Viscosity, Polymer Concentration, DMF/Acetone Ratio and Mean Nanofiber Diameter - Filip, Petr; Zelenkova, Jana; Peer, Petra (Polymers, 2021)
The process of electrospinning polymer solutions depends on many entry parameters, with each having a significant impact on the overall process and where complexity prevents the expression of their interplay. However, under the assumption that most parameters are fixed, it is possible to evaluate the mutual relations between pairs or triples of the chosen parameters. In this case, the experiments were carried out with a copolymer poly(vinylidene-co-hexafluoropropylene) solved in mixed N,N'-dimethylformamide (DMF)/acetone solvent for eight polymer concentrations (8, 10, 12, 15, 18, 21, 24, and 27 wt.%) and five DMF/acetone ratios (1/0, 4/1, 2/1, 1/1, 1/2). Processing of the obtained data (viscosity, mean nanofiber diameter) aimed to determine algebraic expressions relating both to viscosity and a mean nanofiber diameter with polymer concentration, as well as DMF/acetone ratio. Moreover, a master curve relating these parameters with no fitting factors was proposed continuously covering a sufficiently broad range of concentration as well as DMF/acetone ratio. A comparison of algebraic evaluation with the experimental data seems to be very good (the mean deviation for viscosity was about 2%, while, for a mean nanofiber diameter was slightly less than 10%).
Keywords: acetone; N,N’-dimethylformamide; master curve; poly(vinylidene-co-hexafluoropropylene); nanofibrous web; electrospinning